Spin/orbital and magnetic quantum number selective magnetization measurements for CoFeB/MgO multilayer films. (7th September 2016) - Yamazoe, M; Kato, T; Suzuki, K; Adachi, M; Shibayama, A; Hoshi, K; Itou, M; Tsuji, N; Sakurai, Y; Sakurai, H
Abstract: Spin selective magnetic hysteresis (SSMH) curves, orbital selective magnetic hysteresis (OSMH) curves and magnetic quantum number selective SSMH curves are obtained for CoFeB/MgO multilayer films by combining magnetic Compton profile measurements and superconducting quantum interference device (SQUID) magnetometer measurements. Although the SQUID magnetometer measurements do not show perpendicular magnetic anisotropy (PMA) in the CoFeB/MgO multilayer film, PMA behavior is observed in the OSMH and SSMH curves for the | m | = 2 magnetic quantum number states. These facts indicate that magnetization switching behavior is dominated by the orbital magnetization of the | m | = 2 magnetic quantum number states.